2020
DOI: 10.18267/j.aip.138
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Twitter During the COVID-19 Crisis: A Systematic Literature Review

Abstract: At the end of 2019, COVID-19 (Coronavirus 2019) emerged in Wuhan, China, and spread rapidly worldwide. The use of virtual social networks, especially Twitter, has increased due to the present condition. The purpose of the present systematic literature review is to review the investigations on Twitter's role in the COVID-19 crisis. For this purpose, an appropriate search strategy was used to extract the studies conducted in the Web of Science and PubMed databases. In the end, 24 articles were reviewed. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The emotional use of social media such as Twitter to share information may cause a considerable challenge for people's health and ongoing efforts to fight the spread of this disease since it may make this information incorrect and part of conspiracy theories (6). Such theories affect people's way of thinking about vaccination and raise doubts about vaccination (9) because people rely on social media to receive up-todate information in times of crisis (46). In addition, inaccurate information and conspiratorial content can create stronger anti-vaccine beliefs and provoke emotions and changes in people's health behaviors since users fail to pay attention to the validity of the contents.…”
Section: Discussionmentioning
confidence: 99%
“…The emotional use of social media such as Twitter to share information may cause a considerable challenge for people's health and ongoing efforts to fight the spread of this disease since it may make this information incorrect and part of conspiracy theories (6). Such theories affect people's way of thinking about vaccination and raise doubts about vaccination (9) because people rely on social media to receive up-todate information in times of crisis (46). In addition, inaccurate information and conspiratorial content can create stronger anti-vaccine beliefs and provoke emotions and changes in people's health behaviors since users fail to pay attention to the validity of the contents.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many people, such as policymakers, health professionals, politicians, and citizens, are sharing their information, opinions, emotions, personal experience, and content about exposure to COVID-19 on social media and social network services (see e.g. Dalili Shoaei and Dastani, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study on content analysis on Twitter messages also identified the same that acceptance towards COVID-19 vaccine varies across different countries [ 26 ]. At the time of pandemic, social media was used as a tool to understand people opinions and emotions towards outbreak situation and COVID-19 vaccine [ 7 ]. Twitter stands out among social media platforms as a special big data source for public health researchers due to its real-time nature of the data, user-centric content which reflects a high number of users, and the simplicity of accessing and reviewing publicly available information (albeit subject to legal restrictions on redistribution) [ 27 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the time of COVID-19 pandemic, when travel restriction were imposed, people extensively used social media as a public discussion forum to share their opinions on the outbreak [ 6 ]. Not only general public, other people such as health professionals, celebrities and political leaders used Twitter as a health dissemination media by sharing views, authorized information and also personal experiences towards pandemic, as information reaches a wider people within a short duration[ 7 ]. But there are also evidences of misinformation or unauthorized information about COVID-19 being shared in Twitter [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%